2018
DOI: 10.1097/mpg.0000000000001777
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Cholecystectomies for Presumed Biliary Dyskinesia in Children in the United States

Abstract: Despite lack of standardized diagnostic criteria and variable outcomes of surgical intervention reported in pediatric literature, cholecystectomies are commonly performed for children with BD in the United States. Consensus guidelines for the diagnosis and management of this controversial disorder in children are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Pogorelić et al [9] have shown a significant growth in pediatric cholecystectomies over the last twenty years. As demonstrated by the authors and confirmed by several other studies, this growth is attributable to the increase in the prevalence of childhood obesity [10][11][12], showing a correlation between weight increment and the presence of symptomatic cholelithiasis. LC is the gold standard technique for gallbladder diseases in both emergency and elective surgery [13] and also in pediatric surgery, showing short post-operative LOS with low complication rates [1].…”
Section: Introductionsupporting
confidence: 77%
“…Pogorelić et al [9] have shown a significant growth in pediatric cholecystectomies over the last twenty years. As demonstrated by the authors and confirmed by several other studies, this growth is attributable to the increase in the prevalence of childhood obesity [10][11][12], showing a correlation between weight increment and the presence of symptomatic cholelithiasis. LC is the gold standard technique for gallbladder diseases in both emergency and elective surgery [13] and also in pediatric surgery, showing short post-operative LOS with low complication rates [1].…”
Section: Introductionsupporting
confidence: 77%
“…Current trends suggest that the prevalence of biliary tract disease is increasing based on the increasing number of cholecystectomies performed (10)(11)(12). The prevalence of cholelithiasis in healthy children, determined by abdominal ultrasound, is estimated to be 1.9%, whereas the prevalence of biliary dyskinesia in children is unknown (13).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors commonly associated with biliary tract disease in children include older age, female sex, Hispanic ethnicity, obesity, and a positive family history (13,15,(17)(18)(19). A female predominance of cholelithiasis and biliary dyskinesia has been identified in adolescence in most, but not all studies (9)(10)(11)(13)(14)(15)(19)(20)(21). In 1 report, 55% of patients were overweight, obese, or severely obese (15).…”
Section: Discussionmentioning
confidence: 99%
“…Se identificaron un total de 66.380 colecistectomías como diagnóstico de procedimiento primario utilizando un análisis ponderado de 2002 a 2011 en niños. (Matta et al, 2018) La colecistectomía laparoscópica es segura y eficaz en la resolución de los síntomas de la discinesia biliar en niños. En un estudio hecho por Lai et al, se realizó colecistectomía laparoscópica en 215 niños con discinesia biliar, se obtuvo como resultado que el dolor mejoró en 162/181 (89,5%).…”
Section: Patologias De La Vesícula Biliarunclassified